2022
DOI: 10.21203/rs.3.rs-2156625/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of triply periodic minimal surface (TPMS) structure in mesenchymal stem cell differentiation.

Abstract: Tissue engineers have recently been interested in triply periodic minimum surfaces (TPMSs) for use in creating biomimetic porous scaffolds. Improved cell attachment, migration, and proliferation may be achieved with TPMS scaffolds because of its many benefits, such as a high volume to surface area ratio, reduced stress concentration, and enhanced permeability compared to conventional lattice architectures. Some of the crucial tissue-specific parameters, such permeability, Elastic modulus, and pore size, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the perspective of clinical research, AI, ML, and DL bring innovations for professionals in medicines as well as in approaches like in materials sciences drug delivery vehicles (cyclodextrins [ 56 ], Ag nanoparticles [ 57 ], nanogels, TMPS [ 58 ]) structures are simulated by creating the algorithms [ 59 ] to explore the possibilities of their benefits. Beside Miley et al 2021 reported the current issues, prognosis & possible solution for health hazards, clinical testing, approval, and technological uptake by patients and physicians in the domain of smart ingestible electronics.…”
Section: Suggested Potential Solutions To the Drawbacks Of Ai In Heal...mentioning
confidence: 99%
“…In the perspective of clinical research, AI, ML, and DL bring innovations for professionals in medicines as well as in approaches like in materials sciences drug delivery vehicles (cyclodextrins [ 56 ], Ag nanoparticles [ 57 ], nanogels, TMPS [ 58 ]) structures are simulated by creating the algorithms [ 59 ] to explore the possibilities of their benefits. Beside Miley et al 2021 reported the current issues, prognosis & possible solution for health hazards, clinical testing, approval, and technological uptake by patients and physicians in the domain of smart ingestible electronics.…”
Section: Suggested Potential Solutions To the Drawbacks Of Ai In Heal...mentioning
confidence: 99%